Very late-onset of inflammatory bowel disease. A case report - Rycyk, Anna; Kasztelan-Szczerbinska, Beata; Cichoz-Lach, Halina (Journal of Education, Health and Sport, 2022)
Introduction Inflammatory bowel disease (IBD) in most cases is classified into Crohn’s disease (CD) or ulcerative colitis (UC). It appears in 25-35 years of age and the second peak is after fifties. It is very rare to recognize it in the elderly. Case presentation We present a case of a 79-year-old female patient who was admitted to the Chair and Department of Gastroenterology with Endoscopic Unit at the Medical University of Lublin in December 2018 with an acute lower gastrointestinal hemorrhage and dyselectrolytemia. Additionally, she suffered from atrial fibrillation. She has been treated with an anticoagulant therapy and has been receiving dabigatran for many years. After 16 days of diagnostic research and intensive treatment the patient was discharged home with no previous symptoms. After the next 12 days at home our patient returned to the hospital with recurrent gastrointestinal bleeding, abdominal pain and after fainting episode. Digital rectal exam was positive and laboratory test showed anemia again. Colonoscopic findings on admission showed proximally to the splenic flexure blood signs, on Bauhin’s valve a flat ulcer. The histopathological report confirmed the inflammatory bowel disease. After diagnosis of IBD, an effective treatment with mesalazine and prednisone was started. Conclusions Despite the newest clinical trials are more and more common in Crohn’s disease or ulcerative colitis, the elderly patients are mostly excluded from them because of the other accompanying diseases and their burdensome side effects. Choosing the right therapy becomes the main problem in these patients after setting a proper diagnosis which can take years and many unnecessary hospitalizations.